2014
DOI: 10.4048/jbc.2014.17.1.76
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Elastography Using Acoustic Radiation Force Impulse Imaging and Strain Ratio for Breast Tumors

Abstract: PurposeThe aim of this study was to determine whether the combination of B-mode ultrasonography (BUS), acoustic radiation force impulse (ARFI) elastography, and strain ratio (SR) provides better diagnostic performance of breast lesion differentiation than BUS alone.MethodsARFI elastography and SR evaluations were performed on patients with 157 breast lesions diagnosed by BUS from June to September 2013. BUS images were classified according to the Breast Imaging-Reporting and Data System. ARFI elastography was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
1
39
1
1
Order By: Relevance
“…Generally, benign lesions of the breast are harder than normal breast tissue but softer than malignant tumors [4][5][6]11]; however, there are exceptions. False-positive readings may be influenced by benign conditions that display poor elasticity such as scar tissue, hyperplasia, and fibroadenomas with a predominant fibrous component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, benign lesions of the breast are harder than normal breast tissue but softer than malignant tumors [4][5][6]11]; however, there are exceptions. False-positive readings may be influenced by benign conditions that display poor elasticity such as scar tissue, hyperplasia, and fibroadenomas with a predominant fibrous component.…”
Section: Discussionmentioning
confidence: 99%
“…Published reports have shown that UE combined with US can reduce benign biopsies [1,3]. However, reports of the advantages and pitfalls of UE in the assessment of breast lesions have been discrepant [2,[6][7][8]. Therefore, summarization of experiences and further investigation of the role of UE in the assessment of breast lesions is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transverse and longitudinal sonograms with subsequent diameter measurements of the PG were obtained. The volume was calculated automatically by the system using the three longest diameters (measured perpendicularly) and a multiplication factor of 0.52 [16].…”
Section: Radiotherapy Protocolmentioning
confidence: 99%
“…This potentially improves the characterization of tissues and focal lesions in an objective way. VTTQ has been used in diagnosis of hepatic disease and breast lesions [8][9][10][11] , but there are few reports about VTTQ technique in LNs examination 12,13) . Thus we proposed a study to assess the VTTQ technique in differentiating malignant from benign LNs by contrasting with SR.…”
Section: Introductionmentioning
confidence: 99%